IDENTIFICATION OF CHEMICAL ELEMENTS IN SWEET POTATO (IPOMOEA BATATAS L.) AND CASSAVA (MANIHOT ESCULENTA) USING LASER-INDUCED BREAKDOWN SPECTROSCOPY (LIBS) TECHNIQUE: IDENTIFIKASI UNSUR-UNSUR KIMIA PADA UBI JALAR (IPOMOEA BATATAS L) DAN UBI KAYU (MANIHOT ESCULENTA) DENGAN TEKNIK LASER INDUCED BREAKDOWN SPECTROSCOPY (LIBS) - Anggi Eka Safitri; Ivan Tanra (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
Sweet potatoes are the third staple food in Indonesia after rice and corn. Sweet potatoes do not have different harvest periods and there are many types, including sweet potatoes (Ipomoea batatas L) and cassava (Manihot esculenta), resulting in differences in physical and chemical properties. In this research, experiments were carried out using the Laser Induced Shockwave Plasma Spectroscopy (LISPS) technique using an Nd-YAG laser (1064 nm, 10 Hz) operated in Q-Switch mode on dried cassava and sweet potato samples. Research was conducted to identify and compare the chemical element content of the two sweet potato samples. The sample is placed in a chamber made of metal where the air pressure can be vacuumed and varied with a vacuum pump. Plasma is generated by focusing a laser beam (pulse) on the sample surface with a focusing lens through a window. Plasma radiation is detected using a spectrometer equipped with optical fiber. Plasma radiation is detected using a spectrometer equipped with optical fiber. The results obtained from the blood sample were the detection of elements namely calcium (Ca), sodium (Na), and magnesium (Mg).